Learning to be a midwife in the clinical environment; tasks, clinical practicum hours or midwifery relationships. Issue 1 (January 2016) - Ebert, Lyn; Tierney, Olivia; Jones, Donovan
Abstract: Discussions continue within the midwifery profession around the number of and type of clinical experiences required to ensure competent midwifery graduates. Introduction of the three year Bachelor of Midwifery in Australia, almost two decades ago, was intended to reduce the pressure students were under to complete their academic requirements whilst ensuring students developed midwifery practice that encapsulates the philosophical values of midwifery. Currently, midwifery students are mandated to achieve a minimum number of clinical skills and Continuity of Care Experience (CCE) relationships in order to register upon completion of their degree. To achieve these experiences, universities require students to complete a number of clinical practicum hours. Furthermore students are required to demonstrate competent clinical performance of a number of clinical skills. However, there is no evidence to date that a set number of experiences or hours ensures professional competence in the clinical environment. The aim of this paper is to promote discussion regarding the mandated requirements for allocated clinical practicum hours, specified numbers of clinical-based skills and CCE relationships in the context of learning to be a midwife in Australia.